Distribution of Macroinvertebrates for Bioassessment in Sampean River System, East Java-Indonesia - Yuliandari, Widyanti (Jurnal Ilmu Alam dan Lingkungan, 2025)
Water quality degradation in the Sampean River will increase from year to year due to the increase in wastewater production as well as land degradation resulting from population growth and economic developments. Runoff from intensive agricultural systems can impair the quality of catchment waters, with potential ecological implications. Bioassessment of river water using benthic macroinvertebrates is common in developed countries. However, using bioassessment as part of regular monitoring programs in developing countries is scarce. Assessment of river water pollution in Indonesia is mainly conducted by comparing the physico-chemical parameters of water and the standards regulated by law. This study aims to identify the macroinvertebrate community in the Sampean River. Macroinvertebrate data can provide information about the potential application of bioassessment in this river system using macroinvertebrates as bioindicators. Sampling was conducted at 10 locations with two replications. Physico-chemical methods are carried out using parameters: temperature, pH, BOD, ammonium, nitrite, nitrate, and phosphate. Macroinvertebrates were obtained with kick sampling using a standard handset (500 μm pore size) and an adequate 5-minute collection time. Found 21 taxa of Plecoptera. Based on the macroinvertebrate community found in this study, bioassessment is a potential method to be applied in the Sampean River system. However, further research is needed to understand the most suitable approach.